Simultaneous TGF-β and GITR pathway modulation promotes anti-tumor immunity in glioma - Daniela Lorizio; Manuela Silginer; Julia Friesen; Alan L. Epstein; Michael Weller; Patrick Roth (Cancer Immunology, Immunotherapy)
Abstract The immunosuppressive tumor microenvironment of glioblastoma limits the effectiveness of most immunotherapies. Transforming growth factor (TGF)-β signaling drives tumor progression and prevents effective T cell activity. Notably, both regulatory T cells (Tregs) and effector T cells within glioblastoma and other tumors express high levels of the immune checkpoint receptor, glucocorticoid-induced tumor necrosis factor receptor (GITR), which modulates T cell activation and function. Combining GITR agonism with TGF-β inhibition may therefore offer a compelling approach to restore anti-tumor immunity. We evaluated the combined effects of TGF-β inhibition and GITR modulation using two different GITR agonists in syngeneic mouse glioma models. GITR modulation enhanced T cell activation, as shown by increased cytokine secretion and effector T cell proliferation in vitro. Combining GITR modulation with TGF-β inhibition amplified these effects, resulting in significantly stronger immune cell-mediated tumor cell killing compared to single-agent treatments. Combination therapy improved survival of glioma-bearing mice, with a higher fraction of long-term survivors compared to monotherapy. Surviving mice resisted tumor re-challenge, indicating durable adaptive immunity. In summary, dual targeting of TGF-β and GITR pathways synergistically enhances anti-tumor immunity in glioblastoma. This novel combination strategy demonstrates clinical potential by addressing the limitations of existing immunotherapies and offering a promising approach for durable and effective glioblastoma treatment.